Go with the flow: GEF-H1 mediated shear stress mechanotransduction in neutrophils - Fine, Noah (Small GTPases, 2017)
Neutrophils in circulation experience significant shear forces due to blood flow when they tether to the vascular endothelium. Biochemical and biophysical responses of neutrophils to the physical force of flowing blood modulate their behavior and promote tissue recruitment under pro-inflammatory conditions. Neutrophil mechanotransduction responses occur through mechanisms that are not yet fully understood. In our recent work, we showed that GEF-H1, a RhoA specific guanine nucleotide exchange factor (GEF), is required to maintain neutrophil motility and migration in response to shear stress. GEF-H1 re-localizes to flottilin-rich uropods in neutrophils in response to fluid shear stress and promotes spreading and crawling on activated endothelial cells. GEF-H1 drives cellular contractility through myosin light chain (MLC) phosphorylation downstream of the Rho-ROCK signaling axis. We propose that GEF-H1-dependent cell spreading and crawling in shear stress-dependent neutrophil recruitment from the vasculature are due to the specific localization of Rho-induced contractility in the uropod.